Sharia-based Custom and the Politics of Religious Freedom in Contemporary West Sumatra, Indonesia - Taufik, Zulfan (University of Jember, 2024)
Strengthening religious identity politics can be identified as one of the main factors contributing to the decline in religious freedom in Indonesia. While religious identity politics may serve to mobilize certain groups or advance specific agendas, its escalation often comes at the expense of religious freedom and social harmony. Against Indonesia's pluralistic society and decentralized governance system, West Sumatra stands out for its unique blend of Islamic tradition and local adat (customary law), which often challenge the state's legal framework and constitutional guarantees of religious freedom. This article aims to analyze the impact of Sharia-based custom (ABS-SBK)-based identity politics on religious freedom in West Sumatra, focusing on government and social regulations. This study is based on data from interviews, documentation, and analysis of media reports and coverage related to freedom of religion or belief (FoRB) in West Sumatra, as well as a guidebook for the practice of ABS-SBK issued by the Provincial Government of West Sumatra. This article shows that identity politics based on Sharia and local customs has caused many violations of the freedom of religion or belief of minority groups in West Sumatra. In government regulation, local governments have actively enforced mainstream religious and cultural norms and limited expressions and ideas considered contrary to the mainstream. As for the aspect of social regulation, religion-based identity politics is an effective tool for majority groups in limiting the religious freedom of minority groups. Keywords: Identity Politics, Religious Freedom, West Sumatra, Sharia-based Custom, Religious Nationalism